Mechanistic insights into Escherichia coli Alkyl hydroperoxide subunit C (AhpC) and the molecular switch for peroxide robustness - Sek, Mun Foong (2016)
Typical 2-Cys peroxiredoxins (Prxs) are mainly involved in antioxidant defense and the signal transduction pathway of H2O2 by undergoing inactivation once intracellular H2O2 concentrations exceed the threshold. This inactivation mechanism is only present in eukaryotes. In order to glean molecular insights into the sensitive balance behind this mechanism, Escherichia coli mutant and chimeric proteins such as EcAhpC1-186-YFSKHN were generated. A combination of crystallographic and stopped-flow spectroscopic techniques were employed so as to gain greater insight into the essential role of the C- terminal tail in the robustness of prokaryotic Prx. Based on enzymatic and structural assays, the transition steps between the main conformational states of Prx were determined, and a physical linkage between the C-teminal tail and the oligomer interface was established. Furthermore, the C-terminal tail of EcAhpC was identified as a molecular switch between the conformational states and is proposed to be the determining factor of enzymatic inactivation.